Active targeting of RGD-conjugated bioreducible polymer for delivery of oncolytic adenovirus expressing shRNA against IL-8 mRNA - Kim, Jaesung (2011)
Even though oncolytic adenovirus (Ad) has been highlighted in the field of cancer gene therapy, transductional targeting and immune privilege still remain difficult challenges. The recent reports have noted the increasing tendency of adenoviral surface shielding with polymer to overcome the limits of its practical application. We previously reported the potential of the biodegradable polymer, poly(CBA-DAH) (CD) as a promising candidate for efficient gene delivery. To endow the selective-targeting moiety of tumor vasculature to CD, cRGDfC well-known as a ligand for cell-surface integrins on tumor endothelium was conjugated to CD using hetero-bifunctional cross-linker SM(PEG)(n). The cytopathic effects of oncolytic Ad coated with the polymers were much more enhanced dose-dependently when compared with that of naked Ad in cancer cells selectively. Above all, the most potent oncolytic effect was assessed with the treatment of Ad/CD-PEG(500)-RGD in all cancer cells. The enhanced cytopathic effect of Ad/RGD-conjugated polymer was specifically inhibited by blocking antibodies to integrins, but not by blocking antibody to CAR. HT1080 cells treated with Ad/CD-PEG(500)-RGD showed strong induction of apoptosis and suppression of IL-8 and VEGF expression as well. These results suggest that RGD-conjugated bioreducible polymer might be used to deliver oncolytic Ad safely and efficiently for tumor therapy.